Специфика воспитания социальной зрелости учащихся школ-интернатов для детей-сирот - Канишевская, Л. (Социология: теория, методы, маркетинг, 1999)
Discussing the aspects of social upbringing, the author has studied the data of sociological research conducted among the students of boarding schools for orphans. The teachers, tutors and students assessed various living situations according to the questionnaire developed by the Institute of Upbringing Problems of the Academy of Pedagogical Sciences of Ukraine with the assistance of the author. There have been presented the main factors influencing the high school students’ social upbringing asto specific character of the school, social and economic situation in the country.